(untitled) (The Pakistan Development Review, 2002)
After half a century of development experience, one-third of the population of Pakistan today is condemned to struggle below the poverty line, howsoever defined. In absolute terms, this size of the population of the poor is larger than the total population of [West] Pakistan at the time of independence in 1947. The incidence of rural poverty is greater than in urban areas. Iqbal died nine years before the state of Pakistan was established in 1947 and 2 years before the adoption of the Lahore Resolution in 1940. Territorially, the present-day Pakistan is closer to Iqbal’s idea of the Muslim State presented in his famous presidential address at the annual session of the Muslim League held at Allahabad in 1930: “I would like to see the Punjab, North-West Frontier Province, Sindh and Balochistan amalgamated into a single State” [Brelvi (1977), p. 63]. The same, however, would be hard to say in regard to his vision of economy and society. Poverty as a problem, feudalism as the cause and land reform as a solution formed the most important part of this vision.